The path of Handsome Lake : a model of recovery for native people - Walle, Alf H. (Emerald Publishing Limited : IAP-Information Age Pub., 2004)
This group of essays is written to provide a series of suggestions to Native people who seek to deal with alcoholism from the perspective of their unique heritages and with an understanding that the pressures to which Native traditions and societies have been subjected may trigger dysfunctional behavior, such as excessive drinking.